The Journey of Expatriates from pre Expatriation to post Expatriation - Sweta SINGH (Revista de Management Comparat International, 2010)
Business has become increasingly international in the last few decades. The development of research which targets the adjustment of expatriates in the foreign cultures is due to the international movement of human resources. The best way to prevent expatriate failure- provides effective preparation, support and training to the expats and their tailing families. In the literature various theories and models explaining cross-cultural adjustment have been adequately discussed. These theories and models provide a framework that leads to consistent and more powerful findings. This study proposes a theoretical framework based on the basis of comments of previous researchers.